The Role of lncRNAs in Regulating the Intestinal Mucosal Mechanical Barrier. (15th November 2021) - Chen, Shanshan; Zhang, Chi; He, Beihui; He, Ruonan; Xu, Li; Zhang, Shuo
Abstract : lncRNA is a transcript that is more than 200 bp in length. Currently, evidence has shown that lncRNA is of great significance in cell activity, involved in epigenetics, gene transcription, chromatin regulation, etc. The existence of an intestinal mucosal mechanical barrier hinders the invasion of pathogenic bacteria and toxins, maintaining the stability of the intestinal environment. Serious destruction or dysfunction of the mechanical barrier often leads to intestinal diseases. This review first summarizes the ability of lncRNAs to regulate the intestinal mucosal mechanical barrier. We then discussed how lncRNAs participate in various intestinal diseases by regulating the intestinal mucosal mechanical barrier. Finally, we envision its potential as a new marker for diagnosing and treating intestinal inflammatory diseases.